2022
DOI: 10.1111/ele.14099
|View full text |Cite
|
Sign up to set email alerts
|

A global meta‐analysis reveals higher variation in breeding phenology in urban birds than in their non‐urban neighbours

Abstract: Humans have drastically changed environmental conditions on Earth, particularly since the invention of agriculture during the Neolithic Revolution. The footprint of human activity is most pronounced in urban environments, where microclimatic conditions, biogeochemical cycles and sensory landscapes are considerably different from those in non-urban habitats (Grimm et al., 2008). Perhaps not surprisingly, multiple shifts in animal and plant phenotypes have been associated with the novel conditions and selective

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 145 publications
2
29
2
Order By: Relevance
“…Furthermore, a risk of early onset of reproduction is the increased probability of cold snaps, which can be detrimental to insects, and in turn, insectivorous birds (Shipley et al 2020 ). Indeed, a recent meta-analysis has confirmed that the increased variation in breeding phenology of urban birds is a general pattern (Capilla-Lasheras et al 2022 ).…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, a risk of early onset of reproduction is the increased probability of cold snaps, which can be detrimental to insects, and in turn, insectivorous birds (Shipley et al 2020 ). Indeed, a recent meta-analysis has confirmed that the increased variation in breeding phenology of urban birds is a general pattern (Capilla-Lasheras et al 2022 ).…”
Section: Discussionmentioning
confidence: 90%
“…Nevertheless, we should be cautious of such an approach as it is likely to allow the morphologically unique species (in single species niches) to have a larger effect than those with more average morphologies (that are grouped into very large niches). Additionally, other non-morphological traits are likely to be important for surviving urbanization (Capilla-Lasheras et al, 2022) such as flight disturbance distance (Lin et al, 2012), nest site (Spotswood et al, 2021), resilience to noise (Planillo et al, 2020) and dominance (Martin & Bonier, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…One potential explanation for why urban birds may benefit by prioritizing olfactory cues is improved ability to localize anthropogenic food sources. Urban environments are more heterogeneous than natural habitats at small spatial scales [52][53][54][55]. We may speculate that the visual heterogeneity of urban habitats is reduced in winter due to lack of green foliage, while the existing olfactory contrasts might be increased due to lack of volatile compounds released by plants.…”
Section: Discussionmentioning
confidence: 99%